Answer:
![x=(37)/(9)](https://img.qammunity.org/2020/formulas/mathematics/high-school/vk897m5rhlp59dibcz2zv2hi3asb9a1ckq.png)
Explanation:
By the negative exponent rule, you have that:
![((1)/(a))^n=a^(-n)](https://img.qammunity.org/2020/formulas/mathematics/high-school/wybo84ihxu6fclrnm0k4erx4f7d5cjtzg6.png)
By the exponents properties, you know that:
![(m^n)^l=m^((nl))](https://img.qammunity.org/2020/formulas/mathematics/high-school/d2gz0fpbml3sogdrjpv4ve7cd4qmvhsmew.png)
![(m^n)(m^l)=m^((n+l))](https://img.qammunity.org/2020/formulas/mathematics/high-school/9ztq90g1mnvdjj09brd67j002nmiv6udoh.png)
Rewrite 4, 8 and 32 as following:
4=2²
8=2³
32=2⁵
Rewrite the expression:
![(2^2)^((x-7))*(2^3)^((2x-3))=(32)/(2^((x-9)))](https://img.qammunity.org/2020/formulas/mathematics/high-school/fi6xe996vkbpo4ysy253z7e5nmqnlllngi.png)
Keeping on mind the exponents properties, you have:
![(2)^(2(x-7))*(2)^(3(2x-3))=32(2^(-(x-9))](https://img.qammunity.org/2020/formulas/mathematics/high-school/o740foqf2f3lu1cf8tbu6r3jd3tknif8jg.png)
![(2)^(2(x-7))*(2)^(3(2x-3))=(2^5)(2^(-(x-9)))\\\\(2)^((2x-14))*(2)^((6x-9))=(2^5)(2^((-x+9)))\\\\2^(((2x-14)+(6x-9)))=2^((5+(-x+9)))](https://img.qammunity.org/2020/formulas/mathematics/high-school/2lyu7jxz4zo6cd602qyno7uh8d8yzrxqp7.png)
As the bases are equal, then:
![(2x-14)+(6x-9)=5+(-x+9)\\\\2x-14+6x-9=5-x+9\\\\8x-23=14-x\\9x=37](https://img.qammunity.org/2020/formulas/mathematics/high-school/tpmnaouj2pyn8gqrq8zo81pvgny1mncdck.png)
![x=(37)/(9)](https://img.qammunity.org/2020/formulas/mathematics/high-school/vk897m5rhlp59dibcz2zv2hi3asb9a1ckq.png)